Long-Term Outcomes of Bioprosthetic or Mechanical Valve Replacement in End-Stage Renal Disease: A Nationwide Population-Based Retrospective Study - Li, Guan-Yi; Chen, Yun-Yu; Chung, Fa-Po; Chien, Kuo-Liong; Hsu, Chiao-Po; Lin, Yenn-Jiang (Frontiers in Cardiovascular Medicine, 2021)
Background: Valve replacement is associated with worse outcomes in individuals who have end-stage renal disease (ESRD) and require a long-term renal replacement therapy. Prosthetic valve selection in patients with ESRD has remained controversial. Objective: We aimed to investigate long-term outcomes of mechanical and bioprosthetic valve replacement in individuals with ESRD. Methods: We conducted a population-based retrospective cohort study using data obtained from the Taiwan National Health Insurance Research Database. In total, 10202 patients, including 912 ESRD and 9290 non-ESRD patients, were selected after a 1:1 propensity-score matching based on the type of prosthetic valve used. The long-term mortality outcomes were then analyzed. Results: During a median follow-up period of 59.6 months, the Kaplan–Meier survival analysis revealed that ESRD patients who underwent mechanical valve replacement had higher rates of all-cause mortality and CV deaths than those who underwent bioprosthetic valve replacement (Log-rank test, p = 0.03 and 0.02, respectively). Multivariable regression analyses demonstrated that ESRD patients who underwent bioprosthetic valve replacement had lower rates of all-cause mortality (p < 0.001, hazard ratio: 0.88, 95% confidence interval: 0.82-0.93) and cardiovascular (CV) death (p < 0.001, hazard ratio: 0.83, 95% confidence interval: 0.76-0.90) than those who had mechanical valve replacement. Conclusion: Bioprosthetic valve replacement is significantly associated with lower rates of all-cause mortality and CV death in the ESRD population.